Catheter ablation of hemodynamically unstable ventricular tachycardia in ischemic cardiomyopathy using high‐resolution mapping. Issue 4 (17th February 2017) - Kaiser, Lukas; Jularic, Mario; Akbulak, Ruken Özge; Nührich, Jana; Willems, Stephan; Meyer, Christian
Key Clinical Message: Catheter ablation is a recommended therapy option for ventricular tachycardia (VT). The antegrade transseptal approach for targeting VT with left ventricular origin is feasible with the high‐resolution basket catheter. High‐resolution mapping offers the potential to quickly acquire detailed voltage and activation maps. This may help to identify the crucial VT‐substrate even in patients with huge scar areas and hemodynamically unstable VT. Abstract : Catheter ablation is a recommended therapy option for ventricular tachycardia (VT). The antegrade transseptal approach for targeting VT with left ventricular origin is feasible even with the high‐resolution basket catheter. High‐resolution mapping offers the potential to quickly acquire detailed voltage and activation maps and may help to identify the crucial substrate in patients with huge and unclear scar areas suffering from hemodynamically unstable VT.